IDENTIFIKASI PERBANDINGAN NILAI KUALITAS NANAS MD2 DAN JOSAPINE DI SERDANG SELANGOR MALAYSIA - Putra, Rangga Syah; Alridiwirsah, Alridiwirsah; Suprianto, Andi Agus; Lee, Joanna Cheo (Fakultas Pertanian, Universitas Janabadra, 2024)
MD2 and Josapine pineapple are hybrid pineapples. The Josapine pineapple variety has the advantage of having thornless leaves. This study aims to identify the quality values of MD2 and Josapine pineapples with different peeling times in a closed room. This research was carried out on September 19 2023 at the Lepas Tuai Malaysian Agriculture Research and Development Institute (MARDI) Complex in Serdang Selangor, Malaysia. The main ingredients used in this research were MD2 pineapple and Josapine which were obtained from a fruit shop in Serdang Selangor, Malaysia. The tools used in this research were digital scales, blenders, thermometers, measuring cups, Erlenmeyer, spatulas, funnels, glass jars, knives, gloves, chromameters, refractometers, pH meters, and viscometers. This research was conducted using an ordinary completely randomized design (CRD) with two replications and two treatments. All data were analyzed using analysis of variance (ANOVA) and further analysis using the Duncan Multiple Range Test (DMRT) using the SAS program. The results of the analysis of variance showed that differences in pineapple peeling times gave significantly different results in the color of the pineapple skin, thus influencing differences in pineapple quality on the zeroth day (D0) and the third day (D3). The next difference is in the pH and TTA (Titratable Acidity) content of MD2 pineapple which is significantly different from Josapine pineapple in the pineapple quality test treatment on day zero (D0) and day three (D3). Keywords: pineapple, quality, content, color INTISARINanas MD2 dan Josapine merupakan nanas hybrid. Varietas nanas Josapine memiliki keunggulan daunnya tidak berduri. Penelitian ini bertujuan untuk mengidentifikasi nilai kualitas nanas MD2 dan Josapine dengan waktu pengupasan yang berbeda pada ruangan tertutup. Penelitian ini dilaksanakan tanggal 19 September 2023 di Kompleks Lepas Tuai Malaysian Agriculture Research and Development Institute (MARDI) di Serdang Selangor, Malaysia. Bahan utama yang digunakan pada penelitian ini adalah nanas MD2 dan Josapine yang didapatkan dari toko buah yang ada di Serdang Selangor Malaysia. Alat yang digunakan dalam penelitian ini adalah timbangan digital, blender, termometer, gelas ukur, erlenmeyer, spatula, corong, toples kaca, pisau, sarung tangan, chromameter, refraktometer, pH meter, dan viscometer. Penelitian ini dilakukan menggunakan rancangan acak lengkap (RAL) biasa dengan dua ulangan dan dua pelakuan. Semua data dianalisis mennggunakan analisis varians (ANOVA) dan analisis selanjutnya menggunakan Duncan Multiple Range Test (DMRT) dengan menggunakan program SAS. Hasil analisis ragam menunjukkan perbedaan waktu pengupasan buah nanas memberikan hasil yang berbeda nyata pada warna kulit buah nanas sehingga memengaruhi perbedaan kualitas nanas pada pengupasan hari ke-nol (D0) dan hari ke-tiga (D3). Perbedaan selanjutnya terdapat pada pH dan kandungan TTA (Titratable Acidity) nanas MD2 yang berbeda nyata dengan nanas Josapine pada perlakuan uji kualitas nanas pada pengupasan hari ke-nol (D0) dan pengupasan hari ke-tiga (D3). Kata kunci : nanas, kualitas, kandungan, warna